Determination of total flavonoid content in 70% and 96% ethanol extracts of red seaweed (Eucheuma spinosum) obtaned by maceration using UV-Vis spect - Rahma Arenda Syafika; Dwi Kurnia Putri; Suci Rahmawati; Encik Putri Ema Komala; Tri Danang Kurniawan (Indonesian Journal of Health Science, 2026)
Red seaweed (Eucheuma spinosum) is a marine biological resource containing bioactive compounds such as flavonoids with antioxidant potential. This study aimed to determine and compare the total flavonoid content in 70% and 96% ethanol extracts of Eucheuma spinosum obtained by maceration using a UV-Vis spectrophotometric method.This study employed an experimental laboratory design with a comparative approach. Samples were collected from the coastal area of Bengkulu, processed into simplicia, and extracted using 70% and 96% ethanol. Phytochemical screening was conducted to identify flavonoids, while quantitative analysis was performed using UV-Vis spectrophotometry with quercetin as a standard. Data were analyzed using normality, homogeneity, and independent sample t-test.The results showed that total flavonoid content in 70% ethanol extract was 9.2 ± 0.17 mg QE/g (0.92%), while in 96% ethanol extract it was 10.2 ± 0.12 mg QE/g (1.02%). The data were normally distributed and homogeneous (p > 0.05). The independent sample t-test indicated no significant difference between the two groups (p > 0.05).In conclusion, 96% ethanol tends to be more effective for flavonoid extraction, although the difference is not statistically significant.